The impact of intraoperative epiaortic scanning of the ascending aorta on the tactics and outcomes of coronary artery bypass grafting (literature review) - S. L. Andreev; Yu. Yu. Vechersky; V. V. Zatolokin; B. N. Kozlov (Siberian Journal of Clinical and Experimental Medicine, 2026)
This review evaluates the use of intraoperative epiaortic scanning (IES) of the ascending aorta in coronary artery bypass grafting. The diagnostic advantages of IES 3 over traditional palpation and transesophageal echocardiography are discussed, allowing for the detection of atherosclerotic plaques, including mobile and ulcerated ones. Clinical trial data are presented, demonstrating that the use of IES leads to a change in surgical tactics in 5–15% of cases (avoidance of aortic manipulation, use of contactless devices, conversion to off-pump surgery) and a reduction in the relative risk of perioperative stroke by 38–60%. The advantages of specialized systems (MediStim and similar systems) over transesophageal echocardiography, aortic computed tomography, and ultrasound through a special sterile sleeve are discussed, as well as the role of IES in the diagnosis of iatrogenic aortic injuries and in comprehensive intraoperative assessment, which allows for personalized surgical strategy and improved neurological outcomes.